Genotype–phenotype correlation in a cohort of Portuguese patients comprising the entire spectrum of VWD types: impact of NGS - Fidalgo, Teresa; Salvado, Ramon; Corrales, Irene; Pinto, Silva Catarina; Borràs, Nina; Oliveira, Ana; Martinho, Patricia; Ferreira, Gisela; Almeida, Helena; Oliveira, Cristina; Marques, Dalila; Gonçalves, Elsa; Diniz, MJoão; Antunes, Margarida; Tavares, Alice; Caetano, Gonçalo; Kjöllerström, Paula; Maia, Raquel; Sevivas, Teresa; Vidal, Francisco; Ribeiro, Leticia (Thrombosis and Haemostasis, 2016)
The diagnosis of von Willebrand disease (VWD), the most common inherited bleeding disorder, is characterised by a variable bleeding tendency and heterogeneous laboratory phenotype. The sequencing of the entire VWF coding region has not yet become a routine practice in diagnostic laboratories owing to its high costs. Nevertheless, nextgeneration sequencing (NGS) has emerged as an alternative to overcome this limitation. We aimed to determine the correlation of genotype and phenotype in 92 Portuguese individuals from 60 unrelated families with VWD; therefore, we directly sequenced VWF. We compared the classical Sanger sequencing approach and NGS to assess the value-added effect on the analysis of the mutation distribution in different types of VWD. Sixty-two different VWF mutations were identified, 27 of which had not been previously described. NGS detected 26 additional mutations, contributing to a broad overview of the mutant alleles present in each VWD type. Twenty-nine probands (48.3 %) had two or more mutations; in addition, mutations with pleiotropic effects were detected, and NGS allowed an appropriate classification for seven of them. Furthermore, the differential diagnosis between VWD 2B and platelet type VWD (n = 1), Bernard–Soulier syndrome and VWD 2B (n = 1), and mild haemophilia A and VWD 2N (n = 2) was possible. NGS provided an efficient laboratory workflow for analysing VWF. These findings in our cohort of Portuguese patients support the proposal that improving VWD diagnosis strategies will enhance clinical and laboratory approaches, allowing to establish the most appropriate treatment for each patient.
Keywords: Gene mutations; von Willebrand disease; von Willebrand factor; molecular biology methods; NGS